DECISION SUPPORT SYSTEM UNTUK KELAYAKAN PEMBERIAN KREDIT MOTOR DENGAN MENGGUNAKAN METODE SIMPLE ADDITIVE WEIGHTING PADA PERUSAHAAN LEASING - Elyana, Instianti (LPPM Universitas Nusa Mandiri, 2017)
On leasing company engaged in motor credit services and customer use, these services to the loan application will take advantage of the mortgage interest payments. Basically leasing company recruitment section Credit Analyst will analyze the applicant's ability to repay loans and conduct field surveys in order to reduce bad loans. A credit Analysis expected to work quickly and accurately analyze the wealth of data due to the applicant's credit going so it does not close the possibility of error eg calculation errors, misread data. Credit analyst in consumer decision-making activities required creditworthy models of computer-based systems that can provide ease in analyzing the data, the calculation of a credit applicant assessment criteria. The system was designed using Simple Additive weighting method (SAW), which is one method of Fuzzy Multiple Attribute Making Decisions (FMADM). SAW chosen method for calculation of weighted criteria that are not too complicated, making it easy to learn for writers and readers. The system built is expected to help the company's work, especially in the leasing Credit Analyst in conducting the screening credit applicants, can speed up the process of selecting credit applicants and can reduce errors in determining the creditworthiness of consumers.